PENGEMBANGAN APLIKASI MANAJEMEN ARSIP BERBASIS FRAMEWORK LARAVEL DENGAN METODE PROTOTYPING - Dian Yuthika Rizqi; Mohamad Facheri; Muhammad Reza Firmansyah Tanjung; Ahmad Fajar Sidiq (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
The development of village archive management in Indonesia is still largely done manually, causing frequent damage, loss, and time-consuming searches. This study aims to develop a web-based village archive management application using the Laravel framework with the prototyping method. The background of this research is the suboptimal management of archives in Ngadas Village, Malang Regency. The objective is to build an application that can store, search, and secure village archives digitally. The method used is prototyping, consisting of four stages: communication, rapid design, user evaluation, and system refinement. Black-box testing and User Acceptance Test (UAT) were conducted with 5 village officials. The results showed that all functional features run as expected, and the user satisfaction level reached 86.4% (very feasible category). The conclusion is that the application effectively reduces archive search time from an average of 17 minutes to 12 seconds, improves data security, and fits the workflow of village apparatus